Peningkatan Kapasitas Ekonomi Rumah Tangga Miskin Perkotaan Melalui Edukasi Kewirausahaan Sosial - Ayu, Ade Rahma (Jurnal Pengabdian Masyarakat Inovasi, 2025)
Urban poverty in Medan is characterized by limited access to education and formal economic opportunities. This community service program aims to empower poor households in Patumbak Village, Medan Amplas District, through structured social entrepreneurship education. The implementation method utilized the Participatory Technology Development (PTD) approach, which includes partner identification, problem mapping, participatory workshops based on the "Smart-Social Entrepreneur" module, and one month of intensive mentoring. The target partners consisted of 20 poor households, the majority of whom had a low educational background (60% junior high/elementary school graduates) and worked in the informal sector. The results showed a significant increase in the economic and managerial capacity of the partners. A total of 70% of participants reported an increase in income post-intervention, with 30% increasing significantly and 40% increasing gradually. Furthermore, the participant satisfaction rate reached 85% in the satisfied to very satisfied category. Digital transformation was also evident in the partners' ability to utilize social media for product marketing. This service concludes that the integration of managerial training, digital technology, and strengthening the social entrepreneurship mindset is effective in building the economic independence of marginal communities. Continuous collaboration with financial institutions is required to address the micro-capital constraints still faced by the partners.